Enhancing the ductility of cast Mg-Li alloys via dispersed α-Mg phase mitigating the dimension and distribution of interspersed eutectics along grain boundaries - Yu Wang; Ziyang Xia; Jingpeng Xiong; Gang Zeng; Penghao Wang; Lan Luo; Ruizhi Wu; Jian Wang; Yong Liu (Journal of Magnesium and Alloys)
Mg-Li alloys with high lithium concentrations possess a lightweight body-centered cubic (BCC) matrix structure (β-Li). Interspersed eutectics (primarily the reticulated I-phase) often form along phase boundaries (PBs) and grain boundaries (GBs) which strengthen the alloy but cause the loss of ductility due to the brittle behavior of I-phase. By modifying the Li content, we fabricated the (β+α) biphase Mg-Li alloy in which the α-Mg phase with a hexagonal close-packed structure (HCP) is embedded in β-Li matrix, significantly increasing interface density. The high-density interfaces mitigate the distribution and dimension of the I-phase along GBs and PBs. The alloy exhibits enhanced ductility (elongation (EL) = 17.8 %) compared with the alloy without the α-Mg phase (EL = 5.1 %). Structural characterizations unveil the strengthening mechanism of the nanoscale B2 (Li, Mg)3Zn-type precipitates in conjunction with the microscale I-phase. The (Li, Mg)3Zn nanophases augment the yield and ultimate tensile strength of the alloy without a discernible compromise in ductility, predominantly due to gliding dislocations cutting through the precipitates. In contrast, the microscale I-phase presents a formidable barrier to dislocation motion, facilitating dislocation pileups at interfaces and culminating in diminished ductility across the interface. In-situ stretching techniques were employed to scrutinize the microstructural evolution of alloys during tensile deformation, elucidating that the deformation compatibility of alloys correlates with the average size of the I-phase and their distribution along GBs and PBs. Corresponding to the orientation relationship (OR) between the α-Mg and β-Li phases {110}Li//{0001}Mg and <1¯11>Li //<112¯0>Mg, the slip continuity between α-Mg and β-Li on plane pairs of {123}Li-{112¯2}Mg and {112}Li-{112¯2}Mg assures the deformation compatibility through facilitating the deformation across interfaces. Simultaneously, during the stretching process, the dispersed I-phase instigates the emergence of sporadic microcracks, indicating gradual damage evolution. These discoveries offer novel insights into achieving exceptional strength-ductility amalgamations in Mg-Li alloys through microstructural adjustments.